Degree of Approximation of Functions by their Fourier Series in the Besov Space by Matrix Mean - Madhusmita Mohanty; Gokulananda Das; Sanghamitra Beuria (International Journal of Mathematics And its Applications, 2016)
The paper studies the degree of approximation of functions by their Fourier series in the Besov space by matrix mean and this generalizing many known results.